Measuring functioning and disability in Korea: comparing general and dedicated surveys using the ICF as a reference framework - Jiin Kim; Melissa Selb; Youngtae Cho; Wanho Kim; Carla Sabariego (PLoS ONE, 2025)
Introduction Functioning is the third health indicator besides mortality and morbidity. Although Korea periodically collects functioning information, the functioning indicator has not been generated yet. This study aimed to evaluate how functioning information is currently collected in Korea’s health and disability surveys, especially in terms of comparability and comprehensiveness, using the International Classification of Functioning, Disability and Health (ICF) as a reference framework. Methods Data sources included three health and disability surveys in Korea, namely the Population and Housing Census, the Korean National Health and Nutrition Examination Survey, and the Survey on the Living condition of Persons with Disabilities, and two international ICF-based surveys, the International Spinal Cord Injury Survey and the Model Disability Survey. Functioning information was linked by category to the ICF Generic-30 Set utilizing the ICF linking rules. Results Three ICF categories — d450 walking; d510 washing oneself; d540 dressing ̶ were covered by all the data sources. Excluding the Population and Housing Census, which inherently differs from the other data sources, all the surveys addressed six ICF categories — b152 emotional functions; b280 sensation of pain; d240 handling stress and other psychological demands; d450 walking; d510 washing oneself; d540 dressing. The ICF categories b152 emotional functions and b130 energy and drive functions were the most frequently covered across all the surveys. Despite of the common ICF categories, important differences in the operationalization of questions and response options were found. Conclusions The overlap of content of health and disability surveys in Korea enables interoperability with other data sources. Available functioning data can be used for estimating the functioning indicator and metric, as recommended by WHO, which can serve as a valuable epidemiological indicator for complementing mortality and morbidity indicators and for estimating and monitoring rehabilitation or long-term care needs of the Korean population.